Surface quality of the Ficus sp. wood veneers submitted to finishing treatments - Pereira, Karolina do Nascimento; Gonçalez, Joaquim Carlos; Raabe, Joabel; Costa, Alexandre Florian da (Instituto de Ecología, A.C., 2017)
The objective of this investigation was to evaluate the roughness, wettability and the surface color of Ficus sp. genus before and after the process of manual sanding and application of a finishing product (stain). The roughness and color were determined before and after the sanding process and after applying the stain using Surftest SJ 400 Mitutoyo and ColorEye XTH spectrophotometer. The wettability was evaluated by measuring the contact angle between the water drop and the surface of the veneers, using a goniometer Krüss DSA30. The roughness of the veneers, subjected to 180, 240, and 320 sandpaper, decreased after the sanding process and remarkably after stain application. The contact angle was over 90° for all treated samples. Regarding the colorimetry, there was a decrease in L* average values after sanding. After applying the stain, there was a change in color of the wood, from grayish-white to yellow-olive.